Diagnóstico del diseño físico de los puestos de trabajo en las carreras de Agrícola, Agroindustrias y Pecuaria de la ESPAM MFL - Chávez Loor, Wendy Tatiana (2014)
This research was carried out in the teaching, research and linking units of the agricultural, livestock and agro-industries school of the ESPAM MFL, a diagnosis of the physical design at the work place was done, fulfilling the objectives with bibliographical study on the elements of work place designs, proposing a procedure which allow to diagnose jobs and applying a design after improvement programs. Diagnostic tools were used for the development of the research: observation, interview, map and check list. For the implementation of the check list it was taken into account the basic principles of motion economy giving as result that Agriculture school meets 73,33% basic principles, this is due to the laboratories of soil and mechanization unit at 80% that are designed according to the anthropometrics measures of the worker; While fewer school like agro-industries meet 60, as the workshop of flour and feed the Palletizer machine presents deficiency in the design of constituting a not appropriate ergonomic design, establishing a programmed of improvements focused on the physical design of the work place that will help eliminate falls found in the diagnosis and thereby improve security, health and wellbeing of the workers.